[PP.LB03.09] ARTERIAL STIFFNESS IN EXTREME DIPPER TREATED HYPERTENSIVES CORRELATES WITH 24-H BLOOD PRESSURE PARAMETERS. (September 2016) - Amah, G.; Pasteur-Rousseau, A.; Vovelle, A.; Kubis, N.; Bonnin, P.
Abstract : Objective: It has been shown that hypertensive extreme dipper patients have stiffer large arteries than dipper patients. The goal of our study was to correlate the arterial stiffness of treated hypertensive extreme dipper patients according to mean 24-h, mean day-time and mean night-time systolic (SBP), diastolic (DBP), mean (MBP) and pulse blood pressure (PP). Design and method: We selected 987 treated hypertensive patients who underwent 24-h ambulatory blood pressure monitoring. Extreme dipper profile was defined as a mean night-time SBP reduction of at least 20% compared to the mean daytime SBP. Arterial stiffness was measured using carotid-femoral pulse wave velocity (c-f PWV). Patients with secondary hypertension, diabetes mellitus renal failure (glomerular filtration rate < 60 mL/min/1.73 m 2 calculated using the Modification of Diet in Renal Disease formula), atrial fibrillation, clinical suspicion of sleep apnoea, congestive heart failure, history of coronary artery disease, and those working at night were excluded. Correlations between c-f PWV and 24-h, day-time, night-time of SBP, DBP, MBP and PP were analyzed using a linear regression model. Results: 432 patients were selected, including 56 extreme dippers: 17 men (mean age: 52 ± 9 years old) and 39 women (mean age: 58 ± 8 years old) (p = 0.033). Mean BMI was of 27.06+/−5.06 kg/m 2 (17.85–42.19) without any gender difference. Significant positive linear regressions were found only between c-f PWV and mean 24-H SBP (R = 0.59, p < 0.001), mean 24-h PP (R = 0.50, p < 0.001) and mean 24 h MBP (R = 0.41, p = 0.002). Figure. No caption available. Conclusions: In hypertensive extreme dipper patients, the increase in c-f PWV, reflecting increased arterial stiffness, correlates with the elevation of 24-h blood pressure parameters, particularly mean 24-h SBP and mean 24-h PP, although these patients were already treated. These findings should encourage practitioners to control very effectively SBP and the other cardiovascular risk factors to avoid worsening of the arterial stiffness.